(untitled) (Research, Society and Development, 2022)
Spina bifida is defined as a defect in the posterior bone closure of the spine, and the causes are related to the interaction of genetic and environmental factors. Children with spina bifida carry complications that make the pathology a serious public health problem, whose repercussion ranges from their families to the community with which they live. Therefore, the present study proposes to analyze hospitalizations for spina bifida, in the pediatric population, in Brazil and its regions, in the last 5 years. This is a descriptive, retrospective and analytical study about hospitalizations resulting from spina bifida, prepared through secondary data obtained from the Hospital Information System of the Unified Health System, in children under 1 year old to 19 years old, from 2017 to 2021, in Brazil and its macro-regions. In the analyzed period, there were 4,823 hospitalizations for spina bifida, in children aged between 1 year and 19 years, in Brazil. Regarding geographic regions, the largest number of hospitalizations is concentrated in the Northeast region. Regarding the age group, patients younger than 1 year were the most affected. Regarding gender, females predominated. As for the reported ethnicity of the hospitalized patients, the highest number of cases prevailed among those hospitalized of white ethnicity. With this, it is possible to point out patients hospitalized for spina bifida, in children aged between 1 year and 19 years, as a public health problem that deserves the attention of the government and Brazilian society in general.